Fundamental analysis and position trading : evolution of a trader - Bulkowski, Thomas N., 1957- (WILEY, 2013)
Comprehensive coverage of the four major trading styles Evolution of a Trader explores the four trading styles that people use when learning to trade or invest in the stock market. Often, beginners enter the stock market by: -Buying and holding onto a stock (value investing). That works well until the trend ends or a bear market begins. Then they try -Position trading. This is the same as buy-and-hold, except the technique sells positions before a significant trend change occurs.-Swing trading follows when traders increase their frequency of trading, trying to catch the short-term up and down swings. Finally, people try -Day trading by completing their trades in a single day. This series provides comprehensive coverage of the four trading styles by offering numerous tips, sharing discoveries, and discussing specific trading setups to help you become a successful trader or investor as you journey through each style. Trading Basics takes an in-depth look at money management, stops, support and resistance, and offers dozens of tips every trader should know. Fundamental Analysis and Position Trading discusses when to sell a buy-and-hold position, uncovers which fundamentals work best, and uses them to find stocks that become 10-baggers'stocks that climb by 10 times their original value. Swing and Day Trading reveals methods to time the market swings, including specific trading setups, but it covers the basics as well, such as setting up a home trading office and how much money you can make day trading.